Response Surface Methodology for Development and Optimization of Theophylline Pulmonary Delivery System - Ali A. Yas; Yehia I. Khalil; Mohamed S. Mohamed (College of Pharmacy University of Baghdad, 2017)
The aim of the present study was to develop theophylline (TP) inhalable sustained delivery system by preparing solid lipid microparticles using glyceryl behenate (GB) and poloxamer 188 (PX) as a lipid carrier and a surfactant respectively. The method involves loading TP nanoparticles into the lipid using high shear homogenization â€" ultrasonication technique followed by lyophilization. The compositional variations and interactions were evaluated using response surface methodology, a Box â€" Behnken design of experiment (DOE). The DOE constructed using TP (X1), GB (X2) and PX (X3) levels as independent factors. Responses measured were the entrapment efficiency (% EE) (Y1), mass median aerodynamic diameter (MMAD, daer) (Y2), zeta potential (ZP, Î¾) (Y3), fine particles fraction (% FPF) (Y4) and percentage of dissolution efficiency at 420 minutes (% DE420) (Y5). The optimized formula was characterized by differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and X â€" ray powder diffraction (XRD) demonstrated that prolonged release physically due to the loaded TP exists mostly in its crystalline state . Analysis of dissolution data of the optimized formula indicated that the best fitting is with Higuchi model, whereas the mechanism of drug release pattern follows anomalous or non â€" Fickian diffusion. Key words: Glyceryl behenate, solid lipid microparticles, theophylline nanoparticles